HC/AC Ratio as a Predictor of Intrauterine Growth Retardation during Pregnancy: Diagnostic Tool - Naila Ashfaq, Naureen Ghani Ruqia Zafar, Wafa Aalam, Sameer Touqir (Pakistan Journal of Medical & Health Sciences, 2022)
Fetal wellbeing is predicted by his growth assessment during pregnancy. Aim: To evaluate HC/AC ratio as a predictor of intrauterine growth retardation during pregnancy. Study design: Cross sectional study. Methodology: Total of 80 singleton pregnant females with an age ranging from 18-40 years having 20 weeks gestation were enrolled at Combined Military Hospital Kharian. Ultrasound abdomen was done for all enrolled subjects while HC/AC ratio was calculated. All data was noted on Performa. Consent was taken before enrollment. SPSS v.26 analyzed the data. Frequency and percentages were used for quantitative parameters. Results: The mean HC/AC on ultrasound was 1.46±0.14. There were 35 (43.75%) positive for IUGR while 45 (56.25%) were negative for IUGR. Conclusion: It was concluded that HC/AC ratio can serve as a predictor of IUGR during pregnancy with high diagnostic accuracy.